2021
DOI: 10.1002/jia2.25760
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐incurred costs in a differentiated service delivery club intervention compared to standard clinical care in Northwest Tanzania

Abstract: Introduction Placing all clients with a positive diagnosis for HIV on antiretroviral therapy (ART) has cost implications both for patients and health systems, which could, in turn, affect feasibility, sustainability and uptake of new services. Patient‐incurred costs are recognized barriers to healthcare access. Differentiated service delivery (DSD) models in general and community‐based care in particular, could reduce these costs. We aimed to assess patient‐incurred costs of a community‐based DSD intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…People living with HIV in rural Tanzania cross even larger distances, travelling an average of 2.81 hours in total and staying 2.32 hours at the clinic, but spend slightly less on transportation (US$1.09) than in our sample 11. The opportunity cost of illness was also lower (US$3.79), with patients being ill for 16 hours per year on average, which is potentially due to the restriction of the sample to stable patients with HIV.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…People living with HIV in rural Tanzania cross even larger distances, travelling an average of 2.81 hours in total and staying 2.32 hours at the clinic, but spend slightly less on transportation (US$1.09) than in our sample 11. The opportunity cost of illness was also lower (US$3.79), with patients being ill for 16 hours per year on average, which is potentially due to the restriction of the sample to stable patients with HIV.…”
Section: Discussionmentioning
confidence: 53%
“…People living with HIV in rural Tanzania cross even larger distances, travelling an average of 2.81 hours in total and staying 2.32 hours at the clinic, but spend slightly less on transportation (US$1.09) than in our sample. 11 The opportunity cost of illness was also lower (US$3.79), with patients being ill for 16 hours per year on average, which is potentially due to the restriction of the sample to stable patients with HIV. Specifically for patients with cardiovascular diseases, another study reported annual transport costs of US$14 in rural areas and US$24 in urban areas, with average waiting times of 2 hours and 4 hours, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations